School Social Worker Practice Decisions: The Impact of Professional Models, Training, and School Context. Issue 4 (October 2017) - Phillippo, Kate L.; Kelly, Michael S.; Shayman, Emily; Frey, Andy
School social work practice decisions have been the focus of local and national surveys for several decades, most recently in 2014. The need to better understand these findings, particularly school social workers' practice decisions that appear counter to what the field's evidence base indicates is sound practice, led to the current qualitative study. Our inquiry focused on developing a deeper understanding of the impact of professional models (particularly the multitiered systems of support), training, and school context on practice. Data from 16 focus groups (N = 60) revealed that practitioners struggled with contextual constraints upon their work and encountered limited learning opportunities and support, to the extent that they could not consistently implement contemporary practice models. Implications for school social work policy, training, and practice are considered.